Pharmacoepidemiology of ascites and associated complications in hospitalized patients: descriptive observational study - Tasneem, Hirra; Shahbaz, Huda; Sherazi, Bushra Ali (International Current Pharmaceutical Journal, 2015)
Ascites is the pathological accumulation of free fluid in peritoneal cavity. The aim of the present study was to observe the prevalence, clinical management and the assessment of complications associated with ascites in hospitalized patients. A Descriptive Observational Study was conducted at two tertiary care hospitals of Lahore. The data was collected on a data collection form containing questions regarding basic patient information, presenting symptoms, clinical management and associated complications. Verbal informed consent was taken and confidentiality was maintained. Pilot study was performed prior to performance of a full-scale research project. The results are expressed in the form of frequency and percentages. A total of fifty (50) ascitic patients were evaluated during two months. It was slightly more common in females (58%) as compared to males (42%). Common causes of Ascites were Liver Cirrhosis (80%), Chronic Renal Failure (10%), Peritoneal Malignancy and Peritoneal Tuberculosis (4%) each and Cardiac Failure (2%). The mainstay for the first line treatment in patients with cirrhosis includes education regarding dietary sodium restriction and oral diuretics. The major complications associated with Ascites were Protein malnutrition (87%), Mental Confusion (73%), Hepatorenal Syndrome (21%) and Spontaneous Bacterial Perotinitis (8%). In most patients ascites was being managed successfully by limiting the salt intake and provision of a diuretic regimen. As, ascites is a starting point for more serious complications; so, its early diagnosis should be ensured. Social media and NGOs should play their role in creating the awareness regarding this deadly disease. DOI: http://dx.doi.org/10.3329/icpj.v4i2.21482 International Current Pharmaceutical Journal, January 2015, 4(2): 343-346